2003
DOI: 10.1007/s11325-003-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Available Techniques for Objective Assessment of Upper Airway Narrowing in Snoring and Sleep Apnea

Abstract: A number of techniques are available to determine the level of obstructive predominance in snoring and in the obstructive sleep apnea hypopnea syndrome (OSAHS): lateral cephalography, awake endoscopy, awake endoscopy with the Müller maneuver, endoscopy during sleep, endoscopy with nasal continuous positive airway pressure during sleep, fluoroscopy, CT scanning, MR scanning, manometry, and acoustic reflections. Data from different studies using various methods suggest that different patients have different patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 46 publications
1
46
0
3
Order By: Relevance
“…Our results agree with the results reported by cephalometric based studies, fluoroscopy imaging studies, as well as other CT and MR imaging studies. 7,8,11,22 In particular it correlates with data found by Cosentini et al 15 who examined 28 obese severe OSA patients with MRI imaging during wakefulness and reported that the subjects had a very small minimal cross-sectional area (35±16 mm 2 ) which was usually positioned retropalatally.…”
Section: Discussionsupporting
confidence: 82%
“…Our results agree with the results reported by cephalometric based studies, fluoroscopy imaging studies, as well as other CT and MR imaging studies. 7,8,11,22 In particular it correlates with data found by Cosentini et al 15 who examined 28 obese severe OSA patients with MRI imaging during wakefulness and reported that the subjects had a very small minimal cross-sectional area (35±16 mm 2 ) which was usually positioned retropalatally.…”
Section: Discussionsupporting
confidence: 82%
“…Ritter et al [32] in their study concluded that upper airway collapse in response to the inspiratory pressure generated during a Mueller maneuver in both retropalatal and retroglossal regions is mediated primarily through reduction in the lateral airway dimension secondary to the movement of lateral pharyngeal tissue structures. According to the literature, the advantages of Mueller’s maneuver are: easy to perform for patient and examiner, time and cost effective and broadly widespread [31,33]. The disadvantages are: minimally invasive, subjective for both patient and examiner, questionable reproducibility, possible dynamic modification of the upper airway dynamics because of the endoscope presence, which does not necessarily reproduce apnea-hypopnea episodes [21,24,32].…”
Section: Discussionmentioning
confidence: 99%
“…Fiberoptic nasopharyngoscopy during sleep was one of the earliest techniques to study the site of UA collapse during sleep. However, there are striking discrepancies between the fi ndings of different authors [11][12][13][14] . The exposure to radiation during both somnofl uoroscopy and cine computed tomography (CT) will limit the procedure time with these methods [11,12] .…”
Section: Evaluation Of Upper Airway Characteristics During Sleepmentioning
confidence: 96%
“…Moreover, UA collapse can occur simultaneously at multiple sites [10] . Localization of the pharyngeal collapse in the individual SDB patient may be important to optimize the results of local therapies [9][10][11][12] . Fiberoptic nasopharyngoscopy during sleep was one of the earliest techniques to study the site of UA collapse during sleep.…”
Section: Evaluation Of Upper Airway Characteristics During Sleepmentioning
confidence: 99%
See 1 more Smart Citation